11 Investigating the effectiveness of 1, 3 and 5 day holter monitoring: should it be limited to 24 h. (7th October 2015) - Hughes, D; Salim, TS; Hennessy, B; Collison, D; Giblan, G; McClelland, S; Fitzpatrick, N; Hussain, H; McAdam, BF
Abstract : Introduction: Ambulatory ECG – Holter monitoring –provides a continuous 3 lead ECG over the course of 1 to 5 days. The non-invasive Cardiology Department has a very long outpatient waiting list for Cardiac Holter Monitoring with an increasing demand for extended monitoring, from 72 h up to 120 h. Due in part to evidence that the longer the monitor is recording the more arrhythmias are diagnosed. 1, 2 The aim of this audit is to investigate on what day of monitoring an arrhythmia is first detected, thus evaluating the benefit of extended recording. Methods: This audit was carried out in Beaumont Hospital in 2015 with the data collected from the non-invasive cardiology department. A full review of all extended monitoring conducted in 2014 was undertaken. The report for each day was reviewed and documented, which includes information on the indication for the holter monitor, what rhythm was detected and if there were abnormal results what day that they first occurred were documented. Results: In 2014 there were a total of 427 extended holter monitoring performed. Of the 427 results reviewed 167 (39%) were for 48 h, ​126 (30%) were for 72 h and 134 (31%) were for 120 h. 191 of the recordings (45%) had abnormal result. Of the 191 holter reports with abnormal results – 150 (79%) first showed the abnormal results on day 1, 25 (13%) on the second day, 12 (6%) on the third day with 4 (2%) on day 4 and 2 (1%) on day five. Discussion: The results clearly show that the majority of abnormal arrhythmias are found with the first day of monitoring. The number of abnormal results that are detected after the initial 24 h period decreases significantly with only minimal arrhythmias detected on day 4 or 5. Therefore if we were to limit holter monitors to 24–72 h the amount of arrhythmias detected per day of recording would increase dramatically. Other methods of testing, eg loop recorders, may be more suitable for extended monitoring beyond this period. References: Bass EB, Curtiss EI, Arena VC, Hanusa BH, Cecchetti A, Karpf M, Kapoor WN. The duration of Holter monitoring in patients with syncope. Is 24 hours enough? Arch Intern Med. 1990;150(5):1073 Tung CE, Su D, Turakhia MP, Lansberg MG. Diagnostic yield of extended cardiac patch monitoring in patients with stroke or TIA. Front Neurol . 2015;5 :266. doi: 10.3389/fneur.2014.00266. eCollection 2014